2010
DOI: 10.3892/or_00000938
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability and hMLH1 and hMSH2 expression in renal tumors

Abstract: Abstract. Defects in the function of mismatch repair (MMR) genes result in genetic instability, a common feature of malignant progression. This study was conducted to determine the frequency of genetic instability [defined as microsatellite instability (MSI)] and to evaluate the sensitivity/specificity of immunohistochemistry in predicting the deficiency in MMR genes in renal cortical tumors. A total of 51 surgically-resected renal tumors (27 clear cell, 10 papillary, 5 chromophobe carcinomas and 9 oncocytomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The hMSH2 mutations have a higher incidence of extracolonic tumors (6). The defects of both MMR genes are involved in renal carcinogenesis and correlate with the occurrence of microsatellite instability (7).…”
mentioning
confidence: 99%
“…The hMSH2 mutations have a higher incidence of extracolonic tumors (6). The defects of both MMR genes are involved in renal carcinogenesis and correlate with the occurrence of microsatellite instability (7).…”
mentioning
confidence: 99%
“…We measured MMR-D frequencies detected using the OncoPanel algorithm in 20,301 samples across tumor types (Tables 1 and 2 ) and compared them to historical reports of MMR-D prevalence (Tables 1 and 3 , Fig 1 ). 18 - 39 The OncoPanel cohort comprised 13,542 primary biopsies, 4,734 metastatic recurrences, 655 local recurrences, and 1,370 tumors with unspecified biopsy site.…”
Section: Resultsmentioning
confidence: 99%
“… Comparison of mismatch repair–deficient (MMR-D)/microsatellite instability–high (MSI-H) patterns across tumor types. Across all studies described in Table 3 , 18 - 39 the frequency of MMR-D or MSI-H was reported across all six cohorts in nine tumor types: colorectal, endometrial, esophagogastric, head and neck, hepatocellular, prostate, renal cell carcinoma, thyroid cancer, and soft tissue sarcoma. Hepatocellular carcinoma and thyroid cancer had considerably higher MSI-H rates reported in the review by Dudley et al 19 …”
Section: Resultsmentioning
confidence: 99%
“…A deficiency in the cell's ability to repair errors in the DNA sequence that occur during cell division leads to changes in mircosatellite repeats, causing microsatellite instability [7][8][9]. The DNA mismatch repair (MMR) system is a biological pathway essential for maintenance of genomic stability and reduction of microsatellite instability [7].…”
Section: Discussionmentioning
confidence: 99%